Sign properties and axiomatizations of the weighted division value - Whenzong Li; Genjiu Xu; René van den Brink (Tinbergen Institute, 2021)
In this paper, we study axiomatic foundations of the class of weighted division values. Firstly, while keeping efficiency, additivity and the nullifying player property from the original axiomatization of the equal division value, we consider relaxations of symmetry in line with Casajus (2019) to characterize the class of (positively) weighted division values. Secondly, we show that the class of weighted division values can also be characterized by replacing linearity in three axiomatizations of B'eal et al. (2016) with additivity. Finally, we show how strengthening an axiom regarding null, non-negative, respectively nullified players in these three axiomatizations, provides three axiomatizations of the class of positively weighted division values.
Keywords: 330; cooperative game; weighted division values; axiomatization; sign properties